2012
DOI: 10.1097/sap.0b013e31823b68b1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Complex Abdominal Herniorrhaphy

Abstract: A history of multiple abdominal operations is a major predictor of complications and recurrences. If needed, component separation should be used to achieve primary tension-free closure, which helps to reduce the likelihood of hernia recurrences. Our data suggest that mesh reinforcement used concomitantly in a "sandwich" repair with component separation release may lead to reduced recurrence rates and may provide the optimal repair in complex hernia defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 28 publications
1
29
0
4
Order By: Relevance
“…Although the higher initial cost of biologic mesh is discussed in the prior work, this article further extends the ability of the surgeon to judiciously address the patient with complicated hernia with an expanded armamentarium without imparting a financial burden simply based on mesh choice. 9 Recently, a study examined the costs associated with open versus endoscopic component separation. The authors found that overall costs for both techniques were comparable even with the slight additive cost associated specifically with the endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although the higher initial cost of biologic mesh is discussed in the prior work, this article further extends the ability of the surgeon to judiciously address the patient with complicated hernia with an expanded armamentarium without imparting a financial burden simply based on mesh choice. 9 Recently, a study examined the costs associated with open versus endoscopic component separation. The authors found that overall costs for both techniques were comparable even with the slight additive cost associated specifically with the endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent study of 359 patients who had AWR using ADM, with mean follow-up of 28.3 ± 19.0 months, further supports his hypothesis [ 26 ] irrespective of what kind of approach was used and despite all the advances in mesh and in techniques used, the AWR with or without biologic mesh has very high morbidity. In a report of 106 patients [ 27 ] (79 patients of whom had preoperative comorbid conditions), 67 (63 %) patients developed a postoperative complication. Skin necrosis was the most common complication ( n = 21, 19.8 %).…”
Section: Abdominal Wall Defect and Enterocutaneous Fistulasmentioning
confidence: 98%
“…5,6 In addition to these known risk factors, there has been increasing anecdotal and scientific evidence to suggest that biologic dermal matrices contribute to increased incidence of seroma formation. 7,8 Despite these clinical reports, to date there are no studies prospectively comparing seroma incidence in an animal in vivo model.…”
Section: Introductionmentioning
confidence: 98%